2021
DOI: 10.1038/s41586-021-03493-4
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel proteomics reveals host perturbations by SARS-CoV-2 and SARS-CoV

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
671
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 590 publications
(729 citation statements)
references
References 85 publications
51
671
4
3
Order By: Relevance
“…The fact that ATP8B1 was important for both SARS-CoV-2 and MERS-CoV replication highlighted a potentially conserved role for coronaviruses and it would be of high interest to understand the underlying molecular mechanisms. Interestingly, ATP8B1 and its homologous ATP8B2 were recently identified as bindingpartners of SARS-CoV-2 ORF3 and M, respectively 67 , suggesting that the virus might subvert their functions. Of note, TMEM41B, an integral protein of the endoplasmic reticulum known to regulate the formation of autophagosomes, lipid droplets and lipoproteins, was recently shown to be both an essential coronavirus cofactor 25 and a phospholipid scramblase whose deficiency impaired the normal cellular distribution of cholesterol and phosphatidylserine 68 .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that ATP8B1 was important for both SARS-CoV-2 and MERS-CoV replication highlighted a potentially conserved role for coronaviruses and it would be of high interest to understand the underlying molecular mechanisms. Interestingly, ATP8B1 and its homologous ATP8B2 were recently identified as bindingpartners of SARS-CoV-2 ORF3 and M, respectively 67 , suggesting that the virus might subvert their functions. Of note, TMEM41B, an integral protein of the endoplasmic reticulum known to regulate the formation of autophagosomes, lipid droplets and lipoproteins, was recently shown to be both an essential coronavirus cofactor 25 and a phospholipid scramblase whose deficiency impaired the normal cellular distribution of cholesterol and phosphatidylserine 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is worth noting that the ERM proteins anchor plasma membrane proteins to the actin cytoskeleton and hence can direct their accumulation at specific regions of the cell surface, and also that cell fusion proteins expressed by reoviruses have been found to direct actin filament formation to drive cell fusion 49,50 . Two recent studies have reported interaction screens of all proteins expressed by SARS-CoV-2, looking for host proteins that co-precipitate with each viral protein when expressed individually in cultured cells 51,52 . In both cases, the only interaction partners identified for S were the palmitoyltransferase subunits ZDHHC5 and GOLGA7.…”
Section: Discussionmentioning
confidence: 99%
“…The coronaviruses are the largest single stranded RNA viruses known and their genomic RNA encodes around 30 viral proteins 1 . During infection each viral protein performs unique functions and interacts with a range of cellular protein host factors to allow viral proliferation and immune escape [2][3][4][5] . Precise disruption of viral-host factor interactions is an attractive strategy for developing novel antiviral reagents.…”
mentioning
confidence: 99%